Optimizing corn silage quality during hot summer conditions of the tropics: investigating the effect of additives on in-silo fermentation characteristics, nutrient profiles, digestibility and post-ensiling stability - Khan, Nazir Ahmad; Khan, Nadar; Tang, Shaoxun; Tan, Zhiliang (Frontiers in Plant Science, 2023)
Corn crop grown and ensiled at high temperature have lower water soluble carbohydrates (WSC), epiphytic lactic acid bacteria (LAB) population, lactic acid concentration, fermentation quality and aerobic stability. This study systematically investigated the effects of heterofermentative LAB (hetLAB), homofermentative LAB (homLAB), molasses and their mixture (MIX) on in-silo fermentation characteristics, chemical profiles, CNCPS carbohydrate subfractions, in vitro digestibility (DMD), microbial count, and post-ensiling aerobic stability of whole crop corn silage during hot summer (30 to 45ºC) condition. Corn hybrids (P30K08 and DK6789) were ensiled at targeted dry matter (DM) of 330 g/kg for 0, 7, 21, 42, and 150 days in 3 L silos (260 kg of DM/m 3), without additive (CCS) or treated with hetLAB (4×10 6 cfu/g Lactobacillus buchneri), homLAB (1×10 6 cfu/g of L. plantarum), molasses (3% of fresh forage) or MIX (half of individual doses of homLAB, hetLAB and molasses) additives. Compared to CCS, the additives significantly improved silage nutritional and fermentation quality, DM digestibility (in vitro), count of LAB, DM recovery and aerobic stability, and decreased counts of yeast and mold. The homLAB produced corn silage with the highest (P < 0.05) content of lactic acid, and soluble carbohydrates, and lowest contents of acetic acid, NH 3 -N and pH. On the other hand, the hetLAB inoculated silages had the greatest (P < 0.05) value of acetic acids. The greatest numbers of viable LAB were recorded in homLAB and MIX inoculated silages, while the lowest for CCS. The lowest yeast and mold were recorded for hetLAB inoculated silage. The greatest (P < 0.05) DM recovery was recorded for hetLAB (97.3%) and MIX (96.9%), and the lowest for the control silage (92.9%). All additives significantly improved the aerobic stability of corn silage, and the greatest value of >72 h was recorded for hetLAB and MIX inoculats, and the lowest for CSC (25 h). In conclusion, additives application can improve fermentation quality, nutritional value, DM recovery and aerobic stability of whole crop corn silage under hot summer conditions of the tropics. The MIX inoculant showed potential to improve in-silo fermentation, and aerobic stability at the same time.